Seismic risk assessment of existing RC structures using fragility-based approach - Cho Wai Phyo Kyaw; Khin Aye Mon (Researcher and Lecturer Society, 2025)
This study investigates the seismic performance of two groups of existing reinforced concrete (RC) buildings: those designed and constructed according to older standards (pre-code RC buildings) and those designed and constructed in accordance with current seismic code requirements (moderate-code RC buildings). Recognizing the potential seismic vulnerability of these structures, this research aims to develop fragility curves to probabilistically assess their seismic performance. Non-linear time history analysis (NTHA) and incremental dynamic analysis (IDA) are employed, considering inter-story drift ratios (%ISDR) as key engineering demand parameters. These parameters are employed to link structural response to ground motion intensities (PGA) across various hazard levels, including Service Level Earthquake (SLE), Design Basic Earthquake (DBE), and Maximum Considered Earthquake (MCE). Eleven sets of ground motions, selected from the PEER database and matched to the Yangon target response spectrum, are used to simulate seismic loading. A representative 12-story RC frame with two plan aspect ratios is analyzed, considering material and geometric non-linearities. Five performance limit states (Fully operational, Immediate Occupancy, Damage Control, Life Safety, and Collapse Prevention) are defined based on FEMA 356. The developed fragility curves provide valuable insights into the seismic vulnerability of existing RC structures, informing the development of effective seismic risk-mitigating strategies and enhancing the resilience of urban areas.